Digital Tools, Democratic Affordances and Participation in a Networked Party: the Czech Pirate Party - Tomáš Martínek; Michal Malý (Acta Politologica)
The article explores the Czech Pirate Party (CPP), identified as a networked party that utilizes digital participatory tools. The study analyzes how software design and usage norms influence the quality and extent of member participation. The CPP serves as a relevant case study due to its early adoption of digital tools for internal deliberation and voting, as well as its transition from a parliamentary party in 2017 to a governing party in 2021. The research findings indicate that, despite the inclusive nature of the party’s participatory processes, voter turnout remains relatively low. This suggests that inclusivity alone may not be sufficient to increase participation rates. The study also highlights that exclusive membership, involving a more selective process for admitting new members, may contribute to stable participation, though it can also limit the expansion of the party’s membership base. The findings provide insights that may be valuable for further research on digital parties and their internal democratic processes, illustrating how digital platforms can influence member engagement in decision-making.